Proceedings of the 47th ACM Technical Symposium on Computing Science Education 2016
DOI: 10.1145/2839509.2844601
|View full text |Cite
|
Sign up to set email alerts
|

A (Updated) Review of Empiricism at the SIGCSE Technical Symposium

Abstract: The computer science education (CSEd) research community consists of a large group of passionate CS educators who often contribute to other disciplines of CS research. There has been a trend in other disciplines toward more rigorous and empirical evaluation of various hypotheses. Prior investigations of the thencurrent state of CSEd research showed a distinct lack of rigor in the top research publication venues, with most papers falling in the general category of experience reports. In this paper, we present o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 10 publications
3
30
0
1
Order By: Relevance
“…The comparison with Randolph et al's results shows that significantly fewer articles in our sample presented anecdotal or attitudes only results [16]. This could be the result of our limited breadth of analysis relative to Randolph et al, but results reported in Al-Zubidy, comparing their categorization SIGCSE papers to earlier reviews of SIGCSE papers, support the conclusion that CS education research is moving away from superficial results and more towards empirical results [1]. However, the results on the 'positive' methodological indicators (experimental and qualitative), as well as the 'negative' indicator of single group posttest only designs, show no change from Randolph et al's analysis.…”
Section: Comparisons Between Current and Previous Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…The comparison with Randolph et al's results shows that significantly fewer articles in our sample presented anecdotal or attitudes only results [16]. This could be the result of our limited breadth of analysis relative to Randolph et al, but results reported in Al-Zubidy, comparing their categorization SIGCSE papers to earlier reviews of SIGCSE papers, support the conclusion that CS education research is moving away from superficial results and more towards empirical results [1]. However, the results on the 'positive' methodological indicators (experimental and qualitative), as well as the 'negative' indicator of single group posttest only designs, show no change from Randolph et al's analysis.…”
Section: Comparisons Between Current and Previous Resultssupporting
confidence: 63%
“…Lastly, we compared our results to those described in Al-Zubidy et al [1], which categorized articles from the proceedings of SIGCSE with respect to whether or not they reported on an empirical study. Al-Zubidy et al's analysis used the same definition of experimental as used by Randolph et al [16], so the comparison between our results and theirs are shown as well.…”
Section: Comparisons Between Current and Previous Resultsmentioning
confidence: 99%
See 3 more Smart Citations